Do Independent Commissioners Restrain Earning Management and Tax Avoidance? - Nalarreason, Kadek Marlina; Prameswari, Ni Putu Anindya Sarasija (Universitas Kristen Maranatha, 2025)
Purpose – This research seeks to explore the influence of earnings management on tax avoidance, and examine how independent commissioners help to reduce this impact on Indonesia’s non-financial state-owned enterprises (SOE’s) Design/Methodology/Approach – This study adopts a quantitative approach using secondary data collected from the annual and financial reports of non-financial SOEs between 2019 and 2023. The sample consists of 17 companies selected using purposive sampling. The formulated hypotheses are tested using Moderated Regression Analysis (MRA). Findings – The analysis reveals that earnings management significantly affects tax avoidance. Additionally, the presence of independent commissioners helps mitigate this relationship, confirming that good corporate governance can limit aggressive tax planning strategies. Research Limitations/Implications – This study highlights the importance of independent commissioners in monitoring earnings management and tax avoidance practices. The findings offer reference for regulators and companies to improve corporate governance effectiveness. Furthermore, this research opens opportunities for future studies to explore other factors that may influence the relationship between earnings management and tax avoidance. Keywords: Corporate Governance, Earnings Management, Independent Commissioners, SOEs, Tax Avoidance